ANALYSIS OF THE IMPLEMENTATION OF IMPROVEMENT OF TUBE MATERIAL HANDLING TO SPEED UP THE PICKING PROCESS AT THE RAW MATERIAL WAREHOUSE OF PT. DSV SOLUTIONS INDONESIA (SEMARANG BRANCH) - Dinda Ovelyta Hutauruk; Agung Budiatmo (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Warehouses that store various types of materials such as raw materials, semi-finished goods, and finished goods play an important role in the company's logistics system. Warehouse activities are highly dependent on the speed and accuracy of material and information management. This study aims to evaluate the activities of tube material handling strategies in the Raw Material Warehouse of PT DSV Solutions Indonesia Semarang Branch with a focus on identifying activities, impacts on time and costs, as well as risks and obstacles in the tube material picking process. The company's target is to complete 100% within 5 hours, but during July-December 2023 the target has not been achieved. This research uses a qualitative approach, data collection through observation, interviews, and documentation conducted with qualitative analysis. The results of the research on material handling tubes in the Raw Material Warehouse of PT DSV Solutions Indonesia Semarang Branch show that the current storage system is not optimal. The material picking and sorting process is less than optimal when the material is stored in the original box from the customer which contains several SKUs (Stock Keeping Units). As a result, one retrieval process takes 100 minutes and costs Rp 30,720 in employee salaries. In addition, the current storage system risks hindering the achievement of company targets, extending process time, and increasing the risk of material damage. The conclusion of this study is that the tube material handling strategy in the Raw Material Warehouse of PT DSV Solutions Indonesia Semarang Branch is not optimal and needs improvement regarding storage. The use of more organised material handling in tube material storage can improve picking activities and reduce processing time, costs, and the risk of material damage.